Pengaruh npl, car dan tingkat suku bunga terhadap penyaluran kredit perusahaan perbankan yang terdaftar di bursa efek indonesia pada tahun 2009-2011 - Bagust Budiman Supiatno; Raja Adri Satriawan; Desmiawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the influence of NPL (Non Performing Loan), CAR (Capital Adequacy Ratio) and the Interest Rate on Lending. The object under study is a banking group listed on the Indonesia Stock Exchange (2009-2011) with a total number of 72 samples tested for research data.The analytical method used is multiple regression analysis. Before the t test statistic for multiple regression equation, the test is done first classical assumption of data normality, autocorrelation, multicollinearity and heteroscedasticity. Once the data is free from classical assumptions, then the hypothesis test using the t test to see the effect of each independent variable on the dependent variable partially.Pengaruh npl, car dan tingkat suku bunga terhadap penyaluran kredit perusahaan perbankan yang terdaftar di bursa efek indonesia pada tahun 2009-2011Based on the analysis, it is known that Interest Rate influence the Lending. While the Non-Performing Loan (NPL) and the Capital Adequacy Ratio (CAR) had no significant effect on Lending. coefficient of determination study is 37.2% which is still 62.8% more changes in lending as the dependent variable is affected by other variables that are not used in this research model.Keywords: Lending, NPL (Non Performing Loan), CAR (Capital Adequacy Ratio Credit), and Interest Rate.